On the Fekete-Szegö problem for certain analytic functions - Imran Faisal ,; Maslina Darus , (Penerbit ukm, 2009)
Let f(z)-z+ Σ∞an zn be an analytic function in the open unit disk. A sharp upper bound is obtained for a3-μ a2 for the class CSα (β) of strongly close-to-convex functions of order β and type α, for α, β ≥ 0